Bile acid abnormality induced by intestinal dysbiosis might explain lipid metabolism in Parkinson's disease. (January 2020) - Hasuike, Yuhei; Endo, Takuyuki; Koroyasu, Michiyo; Matsui, Misa; Mori, Chiaki; Yamadera, Misaki; Fujimura, Harutoshi; Sakoda, Saburo
Abstract: Intestinal dysbiosis refers to an imbalance in the intestinal flora. The concept of small intestinal bacterial overgrowth (SIBO), a condition of abnormal proliferation of the small intestine microbiota, has been proposed as a form of small intestine dysbiosis. In Parkinson's disease patients, weight loss and metabolic disorders such as lipid abnormalities are frequently encountered. This was a prospective investigation of the presence of SIBO using the lactulose breath test, Parkinson's disease symptoms, medications, abdominal symptoms, and blood data involving 39 Parkinson's disease patients. Of the 39 patients, 19 were positive for SIBO, 16 were negative, and 4 were equivocal. SIBO-positive patients had a significantly smaller dopaminergic drug load (dopamine replacement of Parkinson's disease drug potency) (P = 0.009) and significantly lower serum triglyceride (TG) (P = 0.024) and total bilirubin (P = 0.019) levels. No relationship was seen between the presence or absence of SIBO and motor or abdominal symptoms. The following hypothesis was developed with regard to the possibility that intestinal bacterial overgrowth has various effects that are exhibited via bile acid metabolism in Parkinson's disease patients. Serum bilirubin levels become higher as bilirubin metabolism declines with decreases in the intestinal bacteria. At the same time, bile acid is broken down due to increased intestinal bacteria, and lipid absorption decreases. This induces low serum TG levels and leads to weight loss. By a similar mechanism, there is less absorption of vitamin D as bile acid levels decrease, leading to osteoporosis and fractures. The possibility that some of the non-motor manifestations accompanying Parkinson's disease are caused by intestinal dysbiosis needs to be considered.